Efficacy and safety of long‐term, continuous subcutaneous octreotide infusion for patients with different subtypes of KATP‐channel hyperinsulinism. (6th April 2013) - Yorifuji, Tohru; Kawakita, Rie; Hosokawa, Yuki; Fujimaru, Rika; Matsubara, Kousaku; Aizu, Katsuya; Suzuki, Shigeru; Nagasaka, Hironori; Nishibori, Hironori; Masue, Michiya
Summary Objective To evaluate the efficacy of long‐term, continuous, subcutaneous octreotide infusion for congenital hyperinsulinism caused by mutations in the KATP‐channel genes, KCNJ11 and ABCC8. Patients Fifteen Japanese patients with diazoxide‐unresponsive, KATP‐channel hyperinsulinism. Methods Molecular diagnoses were made by sequencing and multiple ligation‐dependent probe amplification analysis. In patients with paternally inherited, monoallelic mutations, 18F‐DOPA PET scans were performed to determine the location of the lesion. The patients were treated with continuous, subcutaneous octreotide infusion at a dosage of up to 25 μg/kg/day, using an insulin pump to maintain blood glucose levels higher than 3·33 mmol/l. Additional treatments (IV glucose, glucagon or enteral feeding) were administered as needed. The efficacy of the treatment was assessed in patients who received octreotide for 4 months to 5·9 years. Results Three patients had biallelic mutations, and 12 had monoallelic, paternally inherited mutations. Four patients with monoallelic mutations showed diffuse 18F‐DOPA uptake, whereas seven patients showed focal uptake. Octreotide was effective in all the patients. The patients with biallelic mutations required a higher dosage (17–25 μg/kg/day), and two patients required additional treatments. By contrast, the patients with monoallelic mutations required a lower dosage (0·5–21 μg/kg/day) irrespective of the PET results and mostly without additional treatments. Treatment was discontinued in three patients at 2·5, 3·3 and 5·9 years of age, without psychomotor delay. Except for growth deceleration at a higher dosage, no significant adverse effects were noted. Conclusions Long‐term, continuous, subcutaneous octreotide infusion is a feasible alternative to surgery especially for patients with monoallelic KATP‐channel mutations.